Factors associated with online sexually transmissible infection information seeking among young people in Malaysia: an observational study - Mohamad Shakir, Sharina Mahavera; Wong, Li Ping; Abdullah, Khatijah Lim; Adam, Philippe (CSIRO Publishing, 2019)
The Internet is an important resource of information about sexually transmissible infections (STIs) among young people. Little is known of the facilitators of online STI information seeking. This study aimed to identify the factors associated with online STI information seeking among youth in Malaysia. Methods: A cross-sectional online survey was conducted among Malaysian youth aged 18-25 years who were recruited through social media. Results: Among 1530 respondents who completed the survey, 57.1% sought online STI information in the past 12 months mostly from general Internet websites, health websites, and Facebook. Respondents' overall STI knowledge was low. Young people who had higher STI knowledge (OR = 2.47, 95% CI = 1.87-3.25, P = 0.000), had intention-to-seek online STI information (OR = 2.02, 95% CI = 1.23-3.30, P = 0.000), identified as homosexual or bisexual (OR = 1.67, 95% CI = 1.08-2.57, P = 0.020), experienced STI symptoms (OR = 1.51, 95%CI = 1.02-2.22, P = 0.040), were in a relationship (OR = 1.42, 95% CI = 1.08-1.86, P = 0.012) and had high perceived quality of online STI information (OR = 1.41, 95%CI = 1.09-1.83, P = 0.009) were more likely to seek online STI information. Conclusions: Findings suggest the need to increase STI knowledge and perceived quality of online STI information among Malaysian youth. Young people with low STI knowledge, who are heterosexual, sexually active without STI symptoms and single would benefit from reliable sources of online STI information for STI prevention. © 2019 CSIRO.